Impact of home-based palliative care on health care costs and hospital use: A systematic review. Issue 4 (August 2021) - Gonzalez-Jaramillo, Valentina; Fuhrer, Valérie; Gonzalez-Jaramillo, Nathalia; Kopp-Heim, Doris; Eychmüller, Steffen; Maessen, Maud
Abstract: Objective: To assess the effectiveness of home-based palliative care (HBPC) on reducing hospital visits and whether HBPC lowered health care cost. Method: We searched six bibliographic databases (Embase (Ovid); Cochrane Central Register of Controlled Trials; Medline (Ovid); PubMed; Web of Science Core Collection; and, CINAHL) until February 2019 and performed a narrative synthesis of our findings. Results: Of the 1, 426 identified references, 21 articles based on 19 unique studies met our inclusion criteria, which involved 92, 000 participants. In both oncological and non-oncological patients, HBPC consistently reduced the number of hospital visits and their length, as well as hospitalization costs and overall health care costs. Even though home-treated patients consumed more outpatient resources, a higher saving in the hospital costs counterbalanced this. The reduction in overall health care costs was most noticeable for study periods closer to death, with greater reductions in the last 2 months, last month, and last two weeks of life. Significance of results: Stakeholders should recognize HBPC as an intervention that decreases patient care costs at end of life and therefore health care providers should assess the preferences of patients nearing the end-of-life to identify those who will benefit most from HBPC.